Generation of multi-material parts with alternating material layers by Simultaneous Laser Beam Melting of polymers - Laumer, Tobias; Stichel, Thomas; Fanselow, Stephanie; Koopmann, Jonas; Amend, Philipp; Schmidt, Michael (International Conference on Additive Technologies - ICAT 2014, 2014)
By using Additive Manufacturing technologies, like Laser Beam Melting (LBM) of polymers, parts can be realized within single days and necessary modifications can be quickly adapted. With increasing complexity, products are often made out of different polymer materials and the need for multi-material parts is an increasing industry requirement, which cannot be fulfilled by the single material parts realizable by LBM. Therefore, Simultaneous Laser Beam Melting (SLBM) as a new Additive Manufacturing technology offers the possibility to build parts consisting of different polymer materials. The realizable parts combine different material properties, like differing stiffness or chemical resistances, within a single part. Up to now, different materials are deposited next to each other on the building platform, thus the boundary surface between the different polymers is orientated perpendicular to the building direction. For this paper, the polymer powders are alternated in building direction. Thus, the boundary surface is orientated horizontally and is larger, both influencing the boundary surface and resulting part properties, which are analyzed by a high-resolution thermal imaging system and by cross sections.
Keywords: Additive Manufacturing; Simultaneous Laser Beam Melting; Multi-Material Parts